THE STATUTE OF THE CHILD AND ADOLESCENT (ECA) AND THE EXERCISE OF THE RIGHT TO EDUCATION OF ADOLESCENTS IN CONFLICT WITH THE LAW - da Costa, Fernando Henrique Rodrigues; de Oliveira, Luísa Xavier; Martins, Maria da Conceição Rodrigues; dos Santos, Alan Fonseca (Seven Editora, 2025)
The discussion presented in this text analyzes the strengths and weaknesses of the Statute of Children and Adolescents (ECA) in the pursuit of the effective realization of the right to education for adolescents in conflict with the law. Situated at the interface between education and human rights, the study shows that, although the ECA represents a milestone in comprehensive protection, its practical application still faces institutional, political, and structural barriers. The study adopts a qualitative approach, of a biblioFigureic nature, Adorno (1995), Cury (2002), Fernandes and Paludetto (2010), and Queiroz (2017)) and documentary nature (Federal Constitution of 1988; the Law of Guidelines and Bases of Education - LDB nº 9.394/1996); the ECA (Law nº 8.069/1990) and the SINASE (Law nº 12.594/2012). The results highlight the invisibility of adolescents in society and the limitations of public education policies, where the right to education, although legally guaranteed, is not fully realized due to a lack of intersectoral public policies that integrate the areas of education, justice, and social assistance.DOI: https://doi.org/10.56238/sevened2025.038-028